Eloise Armstrong and Eugene Armstrong letter to Carl J. Bendorf regarding bird sightings, November 28, 1988 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1988)
Field notes contributed by Eloise Armstrong and Eugene Armstrong in a letter to Carl J. Bendorf. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed/flatbed